The Effect of Online Learning Policy on the Composition of Bird Species in the Rice Field around Campus 4 of Universitas Ahmad Dahlan - Wicaksana, Ragil Yoga Mandhala; Utami, Inggita (Journal of Biotechnology and Natural Science, 2021)
The Covid-19 pandemic, which began in March 2020, resulted in enacting an online learning policy on campus. This study aimed to analyze the effect of online lecture policies on the composition of birds in the rice fields around Campus 4 of Universitas Ahmad Dahlan (UAD) Yogyakarta. Primary data collection was carried out at six points with the point count method in September 2020 and January 2021. Data analysis was carried out descriptivel by comparing observations with secondary data in September 2019 and January 2020, right before the Covid-19 pandemic. The results showed that the bird species present increased from 14 species to 32 species. The different paddy fields and rice morphology conditions in September and January also affect the bird species present. All birds present were not protected, and only one species, Acridotheres javanicus, was included in the IUCN Red List vulnerable category. Data collection on bird species must be carried out every year to monitor the presence of waterbirds in urban areas.